Study of maternal and perinatal outcome in twin pregnancy at a tertiary care hospital - Patidar, Nisha; Ahari, Priyanka; Damor, Gautam Lal; Choudhary, Neeraj; Jakhar, Balveer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Twin pregnancy refers to the presence of two fetuses in the uterus. The phenomenon of twinning has fascinated mankind throughout its recorded history. The major problems occurring in twin pregnancy are prematurity, Lbw, IUGR, birth trauma, birth asphyxia and congenital anomalies. The most serious risk is preterm delivery, which accounts for most of the increased perinatal mortality, neonatal morbidity, and long-term morbidity of twins. Methods: This prospective observational study included analysis of 250 women with twin pregnancies, over a period from 01st November 2021 to 31st October 2022 with 28 completed weeks of gestation, admitted at PDMC, Udaipur, Rajasthan. Results: In our study 250 twin pregnancies delivered Out of total 15209 deliveries were studied in our institute. incidence of twin pregnancy was 1.64%. The majority of study participants were in the age group 20 to 29 year and delivered between the gestation age 34-37week, multigravida was 51.2% and in primi it was 48.8%. The 4% patients underwent caesarean section and 48% delivered by vaginal delivery. Conclusions: Twin pregnancy is a great challenge to the concerned obstetricians. Complications associated with twin pregnancies cannot be prevented but can be detected early and controlled adequately by proper and prompt management. Timely diagnosis and treatment of nutritional anaemia and pre-eclampsia helps in preventing additional complications. Hence the need for better obstetric care, neonatal care, health services to get a better fruitful outcome.